Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the system of equations using the elimination method, follow these steps:
Given the system:
[tex]\[ 5x + 2y = 3 \][/tex]
[tex]\[ 4x - 8y = 12 \][/tex]
1. Align the equations:
[tex]\[ \begin{array}{l} 5x + 2y = 3 \\ 4x - 8y = 12 \end{array} \][/tex]
2. Multiply the first equation by a factor that will allow the coefficients of [tex]\( y \)[/tex] in both equations to become additive inverses. In this case, we can multiply the first equation by 4 so that the coefficient of [tex]\( y \)[/tex] in the second equation (-8) is the opposite of [tex]\( 8y \)[/tex] in the modified first equation.
[tex]\[ 4(5x + 2y) = 4(3) \][/tex]
[tex]\[ 20x + 8y = 12 \][/tex]
Now our system of equations is:
[tex]\[ \begin{array}{l} 20x + 8y = 12 \\ 4x - 8y = 12 \end{array} \][/tex]
3. Add the two equations together to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{array}{l} (20x + 8y) + (4x - 8y) = 12 + 12 \\ 20x + 8y + 4x - 8y = 24 \\ 24x = 24 \end{array} \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 24x = 24 \][/tex]
[tex]\[ x = \frac{24}{24} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Substitute [tex]\( x = 1 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]:
Using the first equation:
[tex]\[ 5x + 2y = 3 \][/tex]
Substitute [tex]\( x = 1 \)[/tex]:
[tex]\[ 5(1) + 2y = 3 \][/tex]
[tex]\[ 5 + 2y = 3 \][/tex]
[tex]\[ 2y = 3 - 5 \][/tex]
[tex]\[ 2y = -2 \][/tex]
[tex]\[ y = \frac{-2}{2} \][/tex]
[tex]\[ y = -1 \][/tex]
Therefore, the solution to the system of equations is [tex]\( (x, y) = (1, -1) \)[/tex].
So the correct answer is [tex]\( (1, -1) \)[/tex].
Given the system:
[tex]\[ 5x + 2y = 3 \][/tex]
[tex]\[ 4x - 8y = 12 \][/tex]
1. Align the equations:
[tex]\[ \begin{array}{l} 5x + 2y = 3 \\ 4x - 8y = 12 \end{array} \][/tex]
2. Multiply the first equation by a factor that will allow the coefficients of [tex]\( y \)[/tex] in both equations to become additive inverses. In this case, we can multiply the first equation by 4 so that the coefficient of [tex]\( y \)[/tex] in the second equation (-8) is the opposite of [tex]\( 8y \)[/tex] in the modified first equation.
[tex]\[ 4(5x + 2y) = 4(3) \][/tex]
[tex]\[ 20x + 8y = 12 \][/tex]
Now our system of equations is:
[tex]\[ \begin{array}{l} 20x + 8y = 12 \\ 4x - 8y = 12 \end{array} \][/tex]
3. Add the two equations together to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{array}{l} (20x + 8y) + (4x - 8y) = 12 + 12 \\ 20x + 8y + 4x - 8y = 24 \\ 24x = 24 \end{array} \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 24x = 24 \][/tex]
[tex]\[ x = \frac{24}{24} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Substitute [tex]\( x = 1 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]:
Using the first equation:
[tex]\[ 5x + 2y = 3 \][/tex]
Substitute [tex]\( x = 1 \)[/tex]:
[tex]\[ 5(1) + 2y = 3 \][/tex]
[tex]\[ 5 + 2y = 3 \][/tex]
[tex]\[ 2y = 3 - 5 \][/tex]
[tex]\[ 2y = -2 \][/tex]
[tex]\[ y = \frac{-2}{2} \][/tex]
[tex]\[ y = -1 \][/tex]
Therefore, the solution to the system of equations is [tex]\( (x, y) = (1, -1) \)[/tex].
So the correct answer is [tex]\( (1, -1) \)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.